2014
DOI: 10.1039/c3sc52535j
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450-catalyzed insertion of carbenoids into N–H bonds

Abstract: Expanding nature's catalytic repertoire to include reactions important in synthetic chemistry will open new opportunities for ‘green’ chemistry and biosynthesis. We demonstrate enzyme-catalyzed insertion of carbenoids into N-H bonds. This type of bond disconnection, which has no counterpart in nature, can be mediated by variants of the cytochrome P450 from Bacillus megaterium. The N-H insertion reaction takes place in water, provides the desired products in 26-83% yield, forms the single addition product exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
195
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(206 citation statements)
references
References 40 publications
7
195
1
3
Order By: Relevance
“…Engineered heme proteins such as cytochrome P450 enzymes, myoglobin, and cyctochrome C have emerged as excellent catalysts for new‐to‐nature reactions,1, 2 including carbene‐transfer reactions such as cyclopropanations,3, 4, 5, 6, 7 olefinations, and8, 9 N−H,10, 11 Si−H,12 and B−H insertion reactions 13. These enzymes have proven amenable to optimization by both genetic methods and co‐factor replacement 14, 15, 16, 17, 18, 19, 20.…”
mentioning
confidence: 99%
“…Engineered heme proteins such as cytochrome P450 enzymes, myoglobin, and cyctochrome C have emerged as excellent catalysts for new‐to‐nature reactions,1, 2 including carbene‐transfer reactions such as cyclopropanations,3, 4, 5, 6, 7 olefinations, and8, 9 N−H,10, 11 Si−H,12 and B−H insertion reactions 13. These enzymes have proven amenable to optimization by both genetic methods and co‐factor replacement 14, 15, 16, 17, 18, 19, 20.…”
mentioning
confidence: 99%
“…Frances Arnold's group at Caltech (Pasadena, CA) recently demonstrated that altered cofactor sites in enzymes can catalyze new reactions, notably the cyclopropanation of alkene via carbenes on the heme-containing cytochrome P450-BM3 scaffold from B. megaterium, never before observed in biocatalysis (15). Mutation of the conserved axial cysteine to serine enabled further novel catalysis, C-H amination (88) and N-H insertion (89). Lastly, a cytochrome P450 oxidase was discovered that catalyzed nitration of tryptophan derivatives (90).…”
Section: Wwwannualreviewsorg • Biocatalysis: a Status Reportmentioning
confidence: 96%
“…Cytochrome P450-BM3 variants were used to create secondary amines from a primary amine and a carbenoid, more specifically ethyldiazoacetate (89). The reaction is chemoselective: no double insertion to a tertiary amine was observed (Figure 11c) …”
Section: Wwwannualreviewsorg • Biocatalysis: a Status Reportmentioning
confidence: 99%
“…As mall library of structurally distinct P450 BM3 mutants allowed the selective cyclopropanation of ad iverse set of styrenes.T his library was also effective for the insertion of carbenes into N À Hb onds. [17] Preliminary mechanistic studies suggest that Fe II is the resting state of the heme cofactor. This feature presents achallenge when attempting to reduce heme from Fe III to Fe II under physiological conditions,a sc ytochrome P450 enzymes have an elaborate gating mechanism to prevent electron transfer in the absence of substrate.Given the low affinity of the substrates for the proteins active site,t he desired conformational change is not possible.…”
Section: Cytochrome P450smentioning
confidence: 99%